STRATIFICATION OF NARRATION: A STYLISTIC VISION INTO MARY SHELLEY’S FRANKENSTEIN - . RAED FADHIL MUHAMMAD ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
Humans in their different languages, territories and cultures have recourse to the narrative discourse as creative space to preserve their traditions, rituals and visions throughout history. So it is not altogether strange to use the narrative devices for those noble purposes. This may explain the sovereignty of the narrative as a prominent genre in both classical and modern eras. The romantic European nineteenth century is no exception. In addition to the poetic style and poetic devices exercised in verse composition, the Romantic literary circles exploited the narrative style as one mode of expression. Here and elsewhere, the language of the narrative is not merely a set of combinatory well-formed structures; they are the vehicle by and through which the writer and the character(s) convey hisor her ideology or politics of life. These literary verbal visions, in one tradition, lend themselves to text analysis under the rubric of literary stylistics.